Historical-Comparative Analyses of Social Acceptance in the United States, Türkiye, and South Africa - Yigit, Ismail Hakki; Abel, Karin M. (Journal of Ethnic and Cultural Studies, 2025)
Taking a historical-comparative approach, our goal in this paper is to investigate the social acceptance of people in three countries: the United States, Türkiye, and South Africa. More specifically, we are interested in socio-historical developments related to racial/ethnic conflicts and income inequality and their impact on the social acceptance of racially different people, immigrants/foreign workers, and religiously dissimilar individuals. To accomplish our goal, we draw on Contact Theory and use data from the World Values Survey (WVS) and the World Bank. Regarding the former, we include seven survey waves spanning from 1981 to 2022. Our analysis shows that social acceptance varies significantly across the three countries and that the history of racial/ethnic conflict is an important factor in shaping these outcomes. When racial/ethnic conflicts increase, the social acceptance of racially/ethnically different people and immigrants/foreign workers decreases. Also, over the period of interest, the United States displayed the highest overall social acceptance. While racial social acceptance remained relatively stable, the social acceptance of immigrants/foreign workers decreased slightly. Türkiye experienced a decline in social acceptance toward racially/ethnically different people and immigrants/foreign workers. South Africa exhibited an uptick in racial social acceptance but a meaningful drop in the social acceptance of immigrants/foreign workers. As for the relationship between income inequality and social acceptance, the results are mixed. On the whole, this relationship seems to be rather weak.